Evaluation of Anaesthetic Effect of Commercial Basil Ocimum basilicum on Zebrafish (Danio rerio) Embryos - Fabiano Capparucci; Giovanni De Benedetto; Sabrina Natale; Roberta Pecoraro; Carmelo Iaria; Fabio Marino (Fishes, 2022)
Essential oils (EOs) are natural compounds used in various fields such as traditional medicine, gastronomy, and agriculture, often used against plant and animal parasites. In the present study, the toxic and pathological effects of basil (Ocimum basilicum) essential oil on the development of zebrafish embryos was investigated. The manufacturer datasheet reported linalool and eugenol as major compounds. The effects of the essential oil were evaluated through a zebrafish embryo toxicity test (ZFET) following the OECD n°236 guidelines. Embryos were exposed to different essential oil concentrations (50, 100, and 200 μL/L). Results showed mortality effects in the experimental groups in a dose-dependent manner. Moreover, zebrafish exposed to the higher concentration showed several pathological alterations; particularly, delayed hatching, pericardial edema, and a significant reduction of heart rate after 96 h post-fertilization (hpf) compared to the control group. Results reported here suggest an anaesthetic effect of the O. basilicum at low concentrations, due to the possible synergist effect of the main components such as linalool and eugenol which act on the GABAergic system evoking bradycardia.